Custom-Made Computer-Aided-Design/Computer-Aided-Manufacturing Biphasic Calcium-Phosphate Scaffold for Augmentation of an Atrophic Mandibular Anterior Ridge - Francesco Guido Mangano; Piero Antonio Zecca; Ric van Noort; Samvel Apresyan; Giovanna Iezzi; Adriano Piattelli; Aldo Macchi; Carlo Mangano (Case Reports in Dentistry)
This report documents the clinical, radiographic, and histologic outcome of a custom-made computer-aided-design/computer-aided-manufactured (CAD/CAM) scaffold used for the alveolar ridge augmentation of a severely atrophic anterior mandible. Computed tomographic (CT) images of an atrophic anterior mandible were acquired and modified into a 3-dimensional (3D) reconstruction model; this was transferred to a CAD program, where a custom-made scaffold was designed. CAM software generated a set of tool-paths for the manufacture of the scaffold on a computer-numerical-control milling machine into the exact shape of the 3D design. A custom-made scaffold was milled from a synthetic micromacroporous biphasic calcium phosphate (BCP) block. The scaffold closely matched the shape of the defect: this helped to reduce the time for the surgery and contributed to good healing. One year later, newly formed and well-integrated bone was clinically available, and two implants (AnyRidge, MegaGen, Gyeongbuk, South Korea) were placed. The histologic samples retrieved from the implant sites revealed compact mature bone undergoing remodelling, marrow spaces, and newly formed trabecular bone surrounded by residual BCP particles. This study demonstrates that custom-made scaffolds can be fabricated by combining CT scans and CAD/CAM techniques. Further studies on a larger sample of patients are needed to confirm these results.